The Federal Democratic Republic of Ethiopia : Technical Assistance Report-Financial Soundness Indicators Mission. (IMF Staff Country Reports; Country Report, 2020)
The International Monetary Fund's (IMF's) Statistics Department (STA) provided technical assistance (TA) on financial soundness indicators (FSI) to the National Bank of Ethiopia (NBE) during June 15-July 10, 2020. The TA mission took place in response to a request from the authorities, with the support of the IMF's African Department (AFR). Due to the COVID-19 pandemic and travel restrictions, the mission was conducted remotely via video conferences. The mission worked with the staff of the NBE on the development of FSIs that are in line with the IMF's 2019 FSI Guide.1 The main objectives of the mission were to: (i) review the source data, institutional coverage, and accounting and regulatory frameworks supporting the compilation of FSIs; (ii) provide guidance for mapping source data for the banking sector to the FSI reporting templates FS2 and FSD as well as preparing the metadata; and (iii) agree with the authorities on the timeline to begin regular reporting of the FSIs for deposit-takers to STA. The mission also provided technical assistance to the NBE on the compilation of net open positions in foreign currencies.